Za pomoc p. Daje najlepszą odp. POMOCY NA JUTRO!!!!!!!!
1.
a) (²/₇)⁻³ * (-²/₇)⁴ =
b) (³/₅)⁻¹¹ * 0,6⁹ * (³/₅)³=
c)13⁷ : 13⁸ =
d) (2¹/₄)⁹ : (2,25)¹⁰ =

2.
a) ((-1,2)²)⁻¹=
b) (((3¹²/₁₇)⁵)⁰)⁻¹¹=
c) (((-2,49)¹)⁻¹)⁻¹
d) ((-¹/₂)²)⁻¹ * (-¹/₂)

3.
a) (⁵/₃)³ * (³/₁₀)³ * (²/₇)³ * (-14)³=
b) (³⁶/₂₅)⁻³ : (4⁴/₅)⁻³=
c) (⁴/₃)⁻² * (0,75)⁻² * (⁵/₆)⁻² * (1,2)⁻²=
d) (-1,2)⁷ : (0,4)⁷ * (¹/₃)⁷=

POMOCY!!!!!!!!!!!!!!!!! OBLICZENIA I ROZWIĄZANIE

1

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-02T00:04:48+01:00
1.
a) (²/₇)⁻³ * (-²/₇)⁴ =
(-2/7)⁴ = (2/7)⁴, tak jest gdy jest potega parzysta
= (2/7)⁻³ * (2/7)⁴=
= (2/7)¹=
=2/7

b) (³/₅)⁻¹¹ * 0,6⁹ * (³/₅)³=
= (3/5)⁻¹¹ * (3/5)⁹* (3/5)³=
= (3/5)¹ =
= (3/5)

c)13⁷ : 13⁸ =
= 13 ⁻¹=
= 1/13

d) (2¹/₄)⁹ : (2,25)¹⁰ =
= (9/4)⁹ : (9/4)¹⁰=
= (9/4)⁻¹=
= 4/9

2.
a) ((-1,2)²)⁻¹=
= (( -12/10)²)⁻¹=
= ( - 6/5)⁻²=
= (-5/6)²=
= 25/36

b) (((3¹²/₁₇)⁵)⁰)⁻¹¹=
= (63/17)° =
= 1
c) (((-2,49)¹)⁻¹)⁻¹=
= (-2,49)¹=
= (-2,49)
d) ((-¹/₂)²)⁻¹ * (-¹/₂)=
= (-1/2)⁻²*(-1/2)=
= (-1/2)⁻¹=
= (-2)¹ =
= -2

3.
a) (⁵/₃)³ * (³/₁₀)³ * (²/₇)³ * (-14)³=
= [ 5/3 *3/10*2/7*(-14)]³ =
= (-2/3)³ =
= -8/27

b) (³⁶/₂₅)⁻³ : (4⁴/₅)⁻³=
= [ 36/25 : 24/25]⁻³ =
= (3/2)⁻³=
= (2/3)³=
= 8/27

c) (⁴/₃)⁻² * (0,75)⁻² * (⁵/₆)⁻² * (1,2)⁻²=
= (4/3)⁻²* (3/4)⁻²* (5/6)⁻² *(12/10)⁻²=
= [ 4/3*3/4*5/6 *6/5 ]⁻²=
= 1⁻²
= 1²=
=1

d) (-1,2)⁷ : (0,4)⁷ * (¹/₃)⁷=
= (-12/10)⁷ : (4/10)⁷ * (1/3)⁷=
= (-6/5)⁷ : (2/5)⁷ * (1/3)⁷ =
= [(-6/5) :(2/5)* (1/3) ]⁷=
= [(-6/5)*(5/2)*(1/3)]⁷=
= (-1)⁷
= -1